The Nord Stream 2 : Analysis of Its Impact on Energy Security in the European Union - Sedov, Iurii (2021)
This bachelor thesis provides an in-depth overview of the opportunities, challenges, and other important dynamics of the Nord Stream 2 project and the projected impact on the European Union’s energy security. It aims to assess how Nord Stream 2 positively affects energy supply of the European Union by understanding its reliability, advanced technologies, and cost effectiveness when delivering natural gas. This thesis is divided into two parts: theoretical and practical. The theoretical part outlines the benefits of natural gas imports for the European Union through assessing the European gas market, the stakeholders’ and partners’ involvement in the Nord Stream 2 project, and potential beneficiaries of this project. The practical part looks at the constraints the Nord Stream 2 project has faced since its announcement as well as a main driving factor behind the current gas-crisis in Europe. The findings of the thesis raise the importance of the consideration of shifting to natural gas supplies on the way to net-zero and demonstrates how the Nord Stream 2 pipeline project can positively impact the European Union’s energy security in the process.